Interpersonal Realizations of Pedagogic Discourse in Indonesian EFL Classrooms - Sunardi Sunardi; M. Sri Samiati Tarjana; Soepomo Poedjosoedarmo; Riyadi Santosa (Universitas Jambi, Magister Program of English Education Department, 2018)
This paper describes the lexicogrammatical realizations of interpersonal meaning in English as a Foreign Language (EFL) classrooms in Indonesian university context. The realizational grammatical patterns are presented using MOOD system in systemic functional linguistics (SFL). The data of this study were three EFL classrooms taken from three English departments in Indonesian universities in Semarang City. Data analyses were done by transcribing the lectures and then divided them into clauses from which the lexicogrammatical realizations of pedagogic MOOD were identified and classified based on MOOD System as suggested by Halliday & Matthiessen in SFL perspectives. The results of the study show that interpersonally, the clauses used in the EFL classrooms are predominated by declarative clause, interrogative clause, and imperative clause. The predominance of declarative clause is influenced by the teacher-centered teaching method used in the classrooms. This method poses lecturer as an expert and students as novice. In this situation, lecturer dominates in giving information about the learning materials. Besides, interrogative clause is also used by lecturer to know the students’ understanding of the learning materials. Finally, imperative clause is also used to ask students to do something relating to the understanding of the learning materials.